Application Of Functional Analysis Methods To Find Solutions Of NonLinear Equations - Turakulov Kh. Sh (Genius Publishing Group, 2023)
The different expressions of nonlinearity require a separate approach to the analysis of each nonlinear problem, the application of methods for finding its solution, and the practical interpretation of the obtained results.
Keywords: Quasi-linear; differential equation; nonlinear integral equation